Processors Functional Design In Public Interior Spaces (Al-Academy, 2017)
It is general known that any design in various fields such as the interior design in the field of spaces interior for the public and specific buildings that is concern about the use of humans resident , as well as other considerations relating to the organization of design elements and lines of locomotors activity and the validity of appropriate receiving to provide comfort and achieve the requirements of the position in the space of restaurants field of research. The researcher choose the title of this study (processors design career in public spaces), the analytical study of the spaces of restaurants, as one of the public spaces that are running in their general environment of people in various strata , ages and other levels , which is require not only the depend on the mechanism of action but also the suitable processors with the nature of the position and the space size with its users . As the researcher mention above , this research included four chapters, the first chapter contains the research problem and its significance and the objectives of the research and its limits, and then select definitions . The second chapter has dealt with the theoretical framework, including general results signals for the research and as a foundations for analytical processors in space description. The third chapter consisted of field research procedures, which is methodology determined by analytical descriptive methods , then the research community and the selected sample of the selected spaces from world wild web sites, and search tool that it is a application for determine the analytical axes forms , and finally a description the sample and analysis. The fourth chapter put the results of the field research, conclusions and proposals then recommendations. The most important points of the study from the results can be summarized as follows:1.Rectangular came to embody the idea of linear regulation that achieves independence and isolation users have more than one cell assembly and central shorting between users.2. Ease of service delivery staff have space for customers, in this organization, which gives the progress of linear motion and clear and not confusing to navigate, and this organization is optimized in such spaces have elongation.3. Must be diversity in the shape or color of assets in case of repetition boring as it appeared the three samples.4. The shape and size of the internal spaces of the three samples impose the type and size of the form and methods of distribution of assets, in particular pieces of furniture from dining tables and seating seats.5. The possibility of processors available in the first and second samples are wider and larger ones in the third sample is completely non-existent due to lack of space that contains Hits and by the middle wall represented the center of the space.6. The space overlap in the distribution system to achieve visual communication and extension as achieved severity glass in the holes and also achieved Mari , this case has appeared in the first sample specifically